New materialism in art – “new stones” in art@science discourse - Michałowska, Marianna (Humaniora. Czasopismo Internetowe, 2020)
This study is devoted to three artistic projects based on debris found on the shores of the seas and oceans: plastiglomerates discovered in Hawaii by Kelly Jazvac, recycled waste projects off the coast of river Thames by Inge Sluijs, and plastic waste from the coasts of Norway gathered by Þóra Pétursdóttir. The analyzed works are manifestations of the trend called “new materiality” in art. The artists’ goal is to encourage rethinking the status of objects of natural origin that surround us in the context of social relations, especially in the perspective of the nature/culture dichotomy. Cultural objects of natural origin are the result of human action. Stone and mineral formations are a special example in art practice. They can be studied due to their physical properties, but transformed due to contemporary climate change and pollution they turn into an object proving the cultural transformation of the environment. For this reason, stones found in coastal areas can no longer be considered as raw material for geologists, but as part of human life. The innovative and creative presentation of objects at exhibitions in the galleries and museums allows the wide audience to understand the relationship between human activities in the environment and its effects on material changes. By focusing on the physical dimension of the matter used, the artists emphasize the role of marine science and comment on socio-political agencies of things, as well as indicate the need for public engagement in activities for marine issues.